EFEKTIVITAS TEKNIK JARIKUBACA DALAM MENINGKATAN KEMAMPUAN MEMBACA KATA BAGI ANAK DISLEKSIA - Ozila Sandriani, Ganda Sumekar, Yosfan Azwandi (Jurnal Penelitian Pendidikan Khusus, 2013)
The background this research was, there is a child who can not read the word dual vocals at SD N 18 Koto Luar Padang. Jarikubaca Techniques is manner a child for happy reading, the purpose of this study is to prove the effectiveness of jarikubaca in improving the reading skills for dyslexic child at 18 Koto Luar Padang. Type of study is a Single Subject Research with A-B-A desaign. The results of this study is jarikubaca techniques effective to go up of read the word dual vocals for a dyslexic child at SDN 18 Koto Luar Padang.